The European Youth Guarantee: A Preliminary Assessment and Broader Conceptual Implications - Werner Eichhorst; Ulf Rinne (Institute of Labor Economics (IZA), 2017)
This paper assesses the current situation of youth unemployment in the European Union. In this context, the main questions are whether the European Youth Guarantee has had any effects and how the school-to-work transitions of young individuals in Europe could be improved.
Keywords: J08; J13; J21; J24; J38; J61; J68; J88; 330; labor policy; labor market institutions; vocational education and training